Minutes of 25th technical and progress monitoring (TPM) meeting of BRACU new campus (session I) - Brac University (Brac University, 2023)
Minutes of the 25th Technical and Progress Monitoring (TPM) meeting (session I) of BRACU new campus, held on 23rd December, 2019.